Successful pregnancy following the transfer of vitrified blastocyst which developed from poor quality embryos on day 3 - Xiao-jian Zhang; Ye-zhou Yang; Li-hua Min; Qun Lv; Pin Bai; Xiao-jie Li; Mei-xu Liao (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: The selection of pre-embryos for transferred is based on morphological appearance. But some poor quality cleaved embryos also can be cultured to the blastocyst stage and implanted.Objective: To assess the clinical pregnancy outcomes of blastocyst transfer which developed from poor quality embryos. Materials and Methods: A total of 109 cleaved embryos with poor quality were cultured to day 5/day 6 and 27 (24.8%) blastocysts were collected from the 15 cycles/patients undergoing conventional IVF. All the blastocysts were cooling with fast-freezing. Then the blastocysts were warmed for transfer. Results: All of 25 vitrified blastocysts (92.6%) survived after warming and were transferred to 15 patients. Five of the women became pregnant. Conclusion: Our results suggest that vitrified human day 5/day 6 blastocyst transfer which develop from poor quality embryo at day 3 can contribute to increasing cumulative pregnancy rates in assisted reproduction